Left ventricular involvement in arrhythmogenic right ventricular cardiomyopathy. (25th November 2020) - Parashar, N; Sinha, M; Sharma, S; Ramakrishnan, S
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is not an isolated RV disease. Left ventricular (LV) or biventricular involvement is being increasingly diagnosed in such patients. There is available research to show that the LV peak strain calculated from feature tracking (FT) cardiac MRI is impaired even before the impairment of function. If present, such involvement is an adverse prognostic marker. Purpose: The aim of this study is to calculate LV involvement in patients with ARVC using FT cardiac MRI. Methods: 27 patients of ARVC who underwent cardiac MRI with late gadolinium enhancement (LGE) in our department were identified. 10 healthy volunteers (controls) were also assessed using non-contrast cardiac MRI. LV strain analysis was performed using Cvi42 Circle cardiovascular imaging software; and global LV peak radial, circumferential and longitudinal strain values were calculated. Patients were divided into two sub groups: those with preserved LV ejection fraction (LVEF) and those with reduced LVEF. Peak LV strain values were compared between the two groups of ARVC patients; and between ARVC patients with preserved LVEF and healthy volunteers. Results: The LV peak global longitudinal strain (GLS), global circumferential strain (GCS) and global radial strain (GRS) were −17.7±2.47, −18.16±2.65, 31.04±6.07 respectively in healthy volunteers. LV global longitudinal (GLS), circumferential (GCS), and radial strain (GRS) were significantly impaired in ARVC/D patients (GLS: −11.97±4.34%, GCS: −14.35±4.32%, GRS: 22.1±7.39%). ARVC patients were divided into 2 subgroups: the preserved LV ejection fraction (LVEF) group (LVEF ≥55%, n=9) and the reduced LVEF group (LVEF <55%, n=18). In ARVC patients with reduced LVEF, the peak GLS was −9.99±3.94, GCS was −12.88±4.08 and GRS was 19.57±7.56. With preserved LVEF these values were −15.1±3.02, −17.3±3.3 and 27.1±3.67 respectively. In ARVC patients with preserved LVEF, the peak LV strain were impaired when compared with healthy volunteers with significant difference in peak GLS in between the two groups (p=0.05). Conclusion: In patients with ARVC, cardiac MRI feature tracking can detect early LV dysfunction and thus adverse prognostic marker. Even in patients with normal LVEF, GLS was found to be significantly impaired as compared to healthy controls. Funding Acknowledgement: Type of funding source: None